Governance, macroeconomic convergence and development in West Africa Monetary Zone - Adebayo Sunday Adedokun; I. Ogunyemi Olumide; Onyebuchi Iwegbu (FULafia Journal of Social Sciences, 2019)
The study interrogated the relevance of governance for macroeconomic convergence criteria and development in West Africa Monetary Zone (WAMZ) comprising Gambia, Ghana, Guinea, Nigeria and Sierra Leone. The methodology of the study involved the Fully Modified Ordinary Least Square regression using time series data (1996 – 2015) from five countries. The study used five proxies for governance variables, namely, control of corruption, rule of law, government effectiveness, political stability and attraction of investment. The results showed that government effectiveness and political stability did not enhance economic development. the result revealed that rule of law and government effectiveness have appreciably enhanced economic development but control of corruption, political stability and investment attraction have not. The study concluded that for WAMZ to achieve the macroeconomic convergence and stability within its fold, there is need for quality representative democracy that will work through institutional reforms and deliver set targets within and across the member states. The fight against the dark spectra called corruption must be won within a reasonable time frame through strengthening of existing institutional arrangements that are saddled with the responsibility of promoting transparency in public domain.
Keywords: 330; Corruption; Rule of Law; Political Stability; West African Monetary Zone